1992
DOI: 10.1063/1.351982
|View full text |Cite
|
Sign up to set email alerts
|

Disorder/order/disorder Ga0.5In0.5P visible light-emitting diodes

Abstract: A new Ga0.5In0.5P light-emitting diode (LED) with order/disorder/order (DOD) structure has been fabricated by metalorganic chemical vapor deposition. Growth temperature and dopant concentration were successfully used as growth parameters to obtain a heterojunction-equivalent structure. From the 77 K photoluminescence measurement, three peak energies of the DOD structure can be resolved clearly. It is shown that the DOD structure is equivalent to the double-heterojunction structure. The wavelength of the LED oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The spectral peak and the FWHM for the as-grown disordered sample at 20 K were 1.87 eV and 12.14 meV, respectively; those same values were 1.86 eV and 15.11 meV, respectively for the as-grown ordered sample at 20 K (not shown here). Compared to the ordered InGaP alloy, the disordered InGaP alloy exhibited a higher transition energy, as reported elsewhere [23][24][25]. This is due to the electron-hole recombination which occurs in an ordered active layer with a narrower band gap.…”
Section: Resultssupporting
confidence: 49%
“…The spectral peak and the FWHM for the as-grown disordered sample at 20 K were 1.87 eV and 12.14 meV, respectively; those same values were 1.86 eV and 15.11 meV, respectively for the as-grown ordered sample at 20 K (not shown here). Compared to the ordered InGaP alloy, the disordered InGaP alloy exhibited a higher transition energy, as reported elsewhere [23][24][25]. This is due to the electron-hole recombination which occurs in an ordered active layer with a narrower band gap.…”
Section: Resultssupporting
confidence: 49%
“…14, 15 Lee et al demonstrated an order-disorder heterostructure LED using Ga 0.5 In 0.5 P in 1992. 16 Recently, Tang et al 17 have also demonstrated the growth of unicompositional order-disorder heterostructures in Al x In 1-x P. In this work, we have characterized the direct bandgap shift due to ordering in several epitaxial Al x In 1-x P films under a variety of growth conditions and have fabricated LEDs using the order-disorder confinement strategy with high-quality directbandgap Al x In 1-x P.…”
Section: Introductionmentioning
confidence: 93%
“…15 If we assume a similar property in InAlP, disorder/order/disorder heterostructures can be an important tool by which one can independently control the bandgap and electron confinement. [16][17][18] A significant portion of the paper is thus devoted to understanding the microstructure and optical characteristics of ordered InAlP, and the growth conditions that result in strong photoluminescence intensity. We report on the growth and characterization of direct-bandgap InAlP grown at material compositions in which the lattice constant is larger than the GaAs lattice constant.…”
Section: Introductionmentioning
confidence: 99%